2017
DOI: 10.1164/rccm.201609-1817oc
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mandibular Advancement Therapy on Endothelial Function in Severe Obstructive Sleep Apnea

Abstract: In moderately sleepy patients with severe OSA, mandibular advancement therapy reduced OSA severity and related symptoms but had no effect on endothelial function and blood pressure despite high treatment compliance. Clinical trial registered with www.clinicaltrials.gov (NCT 01426607).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
87
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(88 citation statements)
references
References 49 publications
0
87
1
Order By: Relevance
“…As described previously,6 patients with severe OSA (Apnoea–Hypopnoea Index (AHI)>30) and no overt CVD were randomly assigned to receive 2 months of treatment with either a custom-made effective MAD or a sham device with objective measurement of treatment adherence by an embedded microsensor (see online supplementary figure E1). Overnight in-lab polysomnography and blood sample collections were performed at baseline and after the 2-month treatment period.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As described previously,6 patients with severe OSA (Apnoea–Hypopnoea Index (AHI)>30) and no overt CVD were randomly assigned to receive 2 months of treatment with either a custom-made effective MAD or a sham device with objective measurement of treatment adherence by an embedded microsensor (see online supplementary figure E1). Overnight in-lab polysomnography and blood sample collections were performed at baseline and after the 2-month treatment period.…”
Section: Methodsmentioning
confidence: 99%
“…A sample size calculation was performed for the primary endpoints of the main study 6. Only patients with available biomarkers before and after the 2-month intervention were included in the present per-protocol analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three trials reported no effect versus placebo,3, 5, 6 one study reported a reduction in daytime blood pressure,7 and another reported a reduction in nocturnal diastolic blood pressure 4. The sixth study reported no difference between a mandibular advancement device and continuous positive airway pressure, but there was no difference in blood pressures versus baseline with either treatment 8.…”
mentioning
confidence: 99%
“…We identified 6 randomized controlled trials using mandibular advancement devices for sleep apnea with 24‐hour blood pressure as the outcome 3, 4, 5, 6, 7, 8. Three trials reported no effect versus placebo,3, 5, 6 one study reported a reduction in daytime blood pressure,7 and another reported a reduction in nocturnal diastolic blood pressure 4.…”
mentioning
confidence: 99%